The Role of Deep Learning in Developing Inclusive and Multicultural Education in Indonesian Junior High Schools - Zainuddin Zainuddin; Ahmad Rojali; Anis Susanti (Journal on Education, 2025)
This article aims to examine the role of the deep learning model in fostering inclusive and multicultural education in Indonesian junior high schools. Using a literature review approach, the discussion focuses on the essence of deep learning as a comprehensive instructional method that emphasizes conceptual understanding, critical reflection, and meaningful connections in real-world contexts. The study finds that this approach holds significant potential in accommodating students’ diverse backgrounds and promoting cross-cultural understanding. By integrating the principles of inclusion and multiculturalism, deep learning can serve as a strategic framework for realizing transformative, contextual, and equitable learning. This article also presents a conceptual model of inclusive-multicultural learning based on deep learning, which can be adapted to the context of junior high schools in Indonesia.